ANALISIS TEKNOLOGI PENANGKAPAN IKAN PILIHAN DI PANTAI SELATAN PROVINSI JAWA BARAT (The Proper Fishing Technology Analysis At Southern Coast of West Jawa Province) - Dedy H. Sutisna; Daniel R. Monintja; Mulyono S. Baskoro; Sugeng H. Wisudo (Buletin PSP, 2007)
As mandated in Fisheries Act No. 31/2004 about Fisheries, it is stated thatfisheries resources management aimed to improve community welfare especially fishermen and to conserve the fisheries resources and its environment. To keep the capture fisheries bussiness system sustainably efficient and profitable. Beside marketing guarantee, optimalization between fisheries resources stock and fishing effort in each of fishing area. The improvement of capture fisheries must be held based on the existing condition, ie: marketing in determining the priority comodity, maximum sustainable yield and fisheries resources utilization level to determine limit of fisheries resources utilization chance, fishing technology and socio-economic condition to identify the fishermen's earns and absorbtion of labours related to capture fisheries sector. Based on the marketing aspect analysiS, it is determined that the kinds of priority comodity in Southern of West Java Province are lobster, shrimp, tuna, skip jack tuna, and layar. Hence, the potency (MSy) and fisheries resources utilization level of the priority comodity still has very large chance to improve, except lobster has large enough chance.Based on the scoring approach, combined from many technical aspects, financial aspects and social aspect can be concluded that the proper fishing technology in southern waters of West J/lVa Province are: (1) Purse seine, (2) Denish saine, (3) Lines, (4) Gillnet, (5) Trammel net, (6) Boat lift net. To improve the management and utilization of  fisheries resources in southe-rn waters of West Java Province or in Hindia Ocean, it is recommended to implement the improvement of proper fishing technology based an technical aspects, financial aspects, environmental and social aspects.Keywords: the proper fishing technology, Southern waters of West Java Province, fisheries resources